EFFECTIVENESS OF IMPLEMENTATION OF DEATH INSURANCE AND WORK ACCIDENT INSURANCE POLICIES FOR FISHERMEN (Qualitative Study in Cilamaya District, Karawang Regency) - Fany Zanirrah Kharismarani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Fishermen are a group of informal sector workers who face high occupational risks, particularly the risk of work accidents and death at sea. The Indonesian government, through the Social Security Agency (BPJS Ketenagakerjaan), has implemented Death Insurance (JKM) and Work Accident Insurance (JKK) policies for fishermen as part of social protection. However, the effectiveness of these policies' implementation at the local level remains problematic. This study aims to analyze the effectiveness of the implementation of BPJS Ketenagakerjaan's JKM and JKK policies for fishermen in Cilamaya District, Karawang Regency. The study used a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, field observations, and documentation. Research informants included fishermen participating and non-participating in BPJS Ketenagakerjaan, village officials, and representatives of related agencies. The results show that the implementation of the JKM and JKK policies has not been fully effective, characterized by low levels of participation, limited socialization, and fishermen's lack of understanding of the program's benefits. Supporting factors for implementation include local government commitment and ease of registration procedures, while inhibiting factors include the characteristics of fishermen's work, low social security literacy, and dependence on government assistance. This study recommends strengthening policy communication strategies and synergy among stakeholders to increase the effectiveness of social protection for fishermen.